Online Learning Using Block-based Programming to Foster Computational Thinking Abilities during the COVID-19 Pandemic - Amnouychokanant, Virawan; Boonlue, Surapon; Chuathong, Saranya; Thamwipat, Kuntida (International Journal of Emerging Technologies in Learning (iJET), 2021)
The COVID 19 pandemic has affected global education. In Thailand, all educational institutions temporarily closed to prevent the spread of COVID-19. However, teaching and learning still need to be continued. It is necessary to switch the learning activities to online learning. In this study, we designed online learning activities for developing computational thinking (CT) of students and carried out an experiment with 90 participants (first-year students enrolled in a Bachelor of Education Program in educational technology and communications at King Mongkut's University of Technology Thonburi). At the beginning of the experiment, all participants were asked to take a CT test to measure their CT. The test is consistent with other CT tests under validation. During the sessions, all participants were taught by Thunkable. After the experiment, they took the CT test again. The results show that by improving CT through block-based programming projects, students’ performance improved significantly. In conclusion, block-based programming and working in pairs are combinations that can potentially help students to perform better, in turn affecting their performance in projects.